Experimental study of morphofunctional characteristics of the welding anastomosis of the small intestine - Lysenko, V. M.; Glagolieva, A. Yu.; Krestyanov, M. Yu.; Zavertylenko, D. S.; Rublenko, M. V.; Rublenko, S. V.; Radkevych, Ya. S.; Dyadyk, O. O. (Морфологія / Morphologia / Morfologìâ, 2018)
Background. Modern methods of small bowel anastomosis formation, introduced in clinical practice, include the creation of a manual stitch or stapled suture at the site of the intestine connection. Despite the constant development of the technological base aimed to provide effective surgical interventions, the rate of small bowel anastomosis leak still reaches 3%, and strictures are observed in 8% of cases. The fundamental research of the option of anastomosis formation without the use of sutures (stitches, staplers) and provided by electrosurgical device application is a promising direction in experimental and clinical surgery. Objective: to study the functional and morphological characteristics of small bowel anastomoses created by bioelectrowelding device. Methods. Experimental method, clinical observation, morphological method (microscopy and capturing of the samples stained with hematoxylin-eosin, Van Gieson, Mason, PAS-reaction). Results. In 3 experimental animals, a regular general and eating behavior was observed in the postoperative period, the bowel function was restored almost immediately after surgery. One pig developed an increased body temperature (38.80C) and short-term (3 days) bowel paresis associated with the effect of acepromazine. The regeneration process in the anastomosis areas appeared to be stage-wise, which was confirmed by neoangiomatosis and maturation of the connective tissue fibers; contact areas of the serosa membranes in welding anastomoses were hermetic, and the function of surrounding cellular elements was preserved. At the same time, in the stitched portions of the anastomoses, the muffs of fibrous tissue around the threads were visualized, which grew circularly and partially replaced the hyaline tissue. Conclusion. Histologic, microscopic and functional evaluation have demonstrated the reliability and safety of the welded small-bowel anastomosis in the experiment.